The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.2527/jas.2015-0203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding pelleted diets without or with distillers dried grains with solubles on fresh belly characteristics, fat quality, and commercial bacon slicing yields of finishing pigs

Abstract: One hundred ninety-two pigs were blocked by age and stratified by initial BW (25.7 ± 2.3 kg) into pens (2 barrows and 2 gilts/pen), and within blocks, pens were assigned randomly to 1 of 4 treatments in a 2 × 2 factorial arrangement, with main effects of diet form (meal vs. pelleted) and distillers dried grains with solubles (DDGS) inclusion (0% vs. 30%). Pigs were slaughtered after a 91-d feeding trial, and carcasses were fabricated after a 24-h chilling period. Belly dimensions and flop distance were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This appears to indicate that although increased IV reduces slicing yield, it may also result in more inconsistent slicing. This hypothesis was previously suggested by the study by Overholt et al (2016) who reported that the number of slices per kilogram tended to deviate from targeted slice counts dictated by slicing machine settings when slicing bacon with greater IV.…”
Section: Bacon Processing Characteristicsmentioning
confidence: 77%
See 2 more Smart Citations
“…This appears to indicate that although increased IV reduces slicing yield, it may also result in more inconsistent slicing. This hypothesis was previously suggested by the study by Overholt et al (2016) who reported that the number of slices per kilogram tended to deviate from targeted slice counts dictated by slicing machine settings when slicing bacon with greater IV.…”
Section: Bacon Processing Characteristicsmentioning
confidence: 77%
“…After chilling, carcasses were fabricated according to North American Meat Processors Association (NAMP, 2010) specifications for #408 bellies. Fresh bellies were weighed, and length, width, depth, and flop distance measures were obtained using the methods described by Overholt et al (2016). Adipose tissue cores, measuring 2.54 cm in diameter and consisting of all 3 adipose layers, were collected from the anterior end along the dorsal edge of each belly.…”
Section: Bacon Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kyle et al (2014) reported a ~3 unit increase in iodine value and a ~19 cm decrease in flop distance between barrows and boars, which translated to a ~4% decrease in cooked slice yield. However, Tavárez et al (2014) and Overholt et al (2016b) reported no differences in cooked slice yield in pigs fed 0 and 30% dried distillers grains with solubles regardless of a 7 to 8 unit difference in iodine value. One possible explanation for an increase in cooked slice yield in 1.8 compared with 1.2% bacon slabs is the amount of slices that were removed from the 1.2 vs the 1.8% bacon slabs.…”
Section: Discussionmentioning
confidence: 93%
“…Fresh adipose tissue samples were prepared using the procedure described by Overholt et al (2016b). Fat samples were submerged in liquid N 2 until completely frozen and then pulverized and homogenized in a blender (Waring Products, Torrington, CT) until completely powdered.…”
Section: Fatty Acid Profilementioning
confidence: 99%